Knowledge Sharing Untuk Kinerja Perusahaan : Literature Review - Dwi Arini Mandasari; Mochammad Isa Anshori (Universitas Veteran Bangun Nusantara, 2023)
Knowledge sharing has significant benefits for companies when implemented and applied effectively by employees. This research aims to summarize the factors that can influence knowledge sharing and the variables affected by knowledge sharing in improving company performance. The method used is a literature review of previous journal articles related to the research topic. Data collection is done by searching for journal articles online using the Harzing's Publish or Perish article search application. The data analysis method employed is bibliometric analysis using VosViewer 1.6.1.9 software. The factors influencing knowledge sharing include Internal factors, External factors, and Technological factors. Knowledge sharing has a significant impact on company performance, directly and indirectly